The Corporatist Regime, Welfare State Employment, and Gender Pay Inequity. Issue 1 (2nd January 2018) - Koskinen Sandberg, Paula
Abstract: Mainstream economics conceptualizes wages as determined by market forces and reflecting productivity and investments in human capital made by individuals. These views, which have become taken-for-granted explanations of what wages are, hide the underlying dynamics of the gender pay gap and place responsibility on individuals instead of gendered social structures. This article proposes viewing gender pay inequity through a sociological lens, which implies acknowledging the complex societal dynamics and roles of institutions and actors in shaping wages. The Nordic welfare states are often considered women-friendly, providing female citizens with social policies and services that have enabled their extensive participation in paid employment. Simultaneously, the Finnish welfare state has relied heavily on inexpensive labour provided by women, thus actively contributing to the formation of a secondary female-dominated labour market. The secondary status of reproductive work conducted within the public sector has been further strengthened and institutionalized by the Finnish corporatist system via collective agreements. In policy-making, the central actors defend their vested interests through non-decision-making, limiting the scope of decision-making to non-threatening issues. This article discusses the dynamics of the Finnish corporatist regime, welfare-state employment, and the impact of both on gender pay equity in Finnish society.